JR14a: A novel antagonist of C3aR attenuates neuroinflammation in cerebral ischemia-reperfusion injury - Jiutang Tang; Nueraili Maihemuti; Yu Fang; Junyi Tan; Mengjie Jia; Qinglan Mu; Keli Huang; Hui Gan; Jing Zhao (Brain Research Bulletin, 2024)
Cerebral ischemia-reperfusion injury (CIRI), a prevalent stroke-related complication, can lead to severe brain damage. Inflammation is a crucial factor in CIRI pathogenesis, and the complement component 3a receptor (C3aR) could be a key mediator in the post-CIRI inflammatory cascade. In this study, the role of C3aR in CIRI was investigated utilizing a middle cerebral artery occlusion (MCAO) model in C3aR knockout (KO) mice. Magnetic resonance imaging (MRI) and neurofunctional assessments revealed that C3aR KO mice exhibited significantly diminished cerebral infarction and improved neurological impairments. Consequently, the focus shifted to searching for a small molecule antagonist of C3aR. JR14a, a new potent thiophene antagonist of C3aR, was injected intraperitoneally into mice 1-h post-MCAO model implementation. The mass spectrometry (MS) results indicated the ability of JR14a to penetrate the blood-brain barrier. Subsequent TTC staining and neurofunctional assessments revealed the efficacy of JR14a in reducing cerebral infarct volume and neurological impairment following MCAO. In addition, immunofluorescence (IF) and immunohistochemistry (IHC) demonstrated attenuated microglial activation, neutrophil infiltration, and blood-brain barrier disruption by JR14a in the MCAO model. Furthermore, enzyme-linked immunosorbent assay (ELISA) and Western blotting supported the role of JR14a in downregulating the expression levels of C3aR, tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6), as well as the phosphorylation of p65. In conclusion, the findings suggested that C3aR could be a potential therapeutic target for CIRI, and JR14a emerged as a promising treatment candidate.